2001
DOI: 10.1016/s0022-2275(20)31623-0
|View full text |Cite
|
Sign up to set email alerts
|

Fate of intravenously administered squalene and plant sterols in human subjects

Abstract: We have studied metabolism of plant sterols and squalene administered intravenously in the form of lipid emulsion mimicking chylomicrons (CM). The CM-like lipid emulsion was prepared by dissolving squalene in commercially available Intralipid ® . The emulsion was given as an intravenous bolus injection of 30 ml containing 6.3 mg of cholesterol, 1.9 mg of campesterol, 5.7 mg of sitosterol, 1.6 mg of stigmasterol, 18.1 mg of squalene, and 6 g of triglycerides in six healthy volunteers. Blood samples were drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In humans and animal trials, intravenous administration of SQ emulsion is safe and well-tolerated, with a slower clearance from the circulation compared to triglycerides and plant sterols. 38,61 SQ is a safe, effective, and preferred vaccine adjuvant, 37,62 as it improves antigen uptake by immune cells and evokes humoral and cell-mediated immunity. 63 Immune-modulating treatments in severe COVID-19 cases and antioxidant applications are considered as potential treatment strategies.…”
Section: In Vivo Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In humans and animal trials, intravenous administration of SQ emulsion is safe and well-tolerated, with a slower clearance from the circulation compared to triglycerides and plant sterols. 38,61 SQ is a safe, effective, and preferred vaccine adjuvant, 37,62 as it improves antigen uptake by immune cells and evokes humoral and cell-mediated immunity. 63 Immune-modulating treatments in severe COVID-19 cases and antioxidant applications are considered as potential treatment strategies.…”
Section: In Vivo Resultsmentioning
confidence: 99%
“…Toxicity or hypersensitive reaction was not reported. 38 In addition, in another study, vaccination with a subunit influenza vaccine with the MF59 adjuvant showed no antisqualene antibodies nor enhanced pre‐existing antisqualene antibody titers. It confirmed that antisqualene antibodies are not increased by immunization with vaccines with the MF59 adjuvant.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations